Studies on the interaction between Mycobacterium avium subsp. paratuberculosis and bovine mastitis associated Escherichia coli in a mammary epithelial cell model and identification of passive shedding in small ruminants - Schwarz, David Germano Gonçalves (2016)
Mastitis caused by Escherichia coli can intensely stimulate the immune system and rapidly trigger inflammation in the mammary gland. In contrast, Mycobacterium avium subsp. paratuberculosis (MAP), the etiological agent of paratuberculosis, characterized by chronic granulomatous enteritis, can infect the mammary gland without intensely stimulating the inflammatory response. The interaction of these two species in the mammary gland is still unknown. In some cases, both the elimination of MAP by milk and faeces may occur passively, either through ascending infection of the mammary gland or through ingestion of MAP, respectively. These animals are called passive- shedders and are important as a source of infection to susceptible animals in the herd. The aim of this study was to investigate the relationship between MAP and E. coli in mammary gland cells under experimental conditions and verify the presence of passive- shedder animals. The relationship between a K-10 strain of MAP and E. coli isolated from mastitic milk in mammary epithelial cell lines was evaluated. Cells previously infected by MAP decreased E. coli invasiveness during 120min experimentation. However, the efficiency of E. coli translocation was not compromised, nor was the viability of the MAC-T cells. In contrast, cells previously infected by E. coli showed increased basal-apical translocation capacity of MAP up to 30 min and decreased at 120 min postinfection. Quantification of cytokines showed that IL-1β expression at 120 min was significantly increased in cells infected by MAP + E. coli and E. coli only. Expression of MAPKp 38 and IL-10 were not significant, regardless of time postinfection. To determine the occurrence of passive-shedders, 10 properties were previously investigated for MAP detection. Thirteen goats were positive by faeces culture and/or milk PCR. Among the positive animals, four (4/13) were evaluated by IS900-PCR, feces culture, milk and tissue culture and serology (ELISA). All the results were negative over a one-year period, demonstrating that the animals performed pass- through phenomenon and upward contamination of the mammary gland without becoming infected. Together, these results indicate that the presence of MAP in mammary cells may hamper capacity of E. coli invasion, but when within the mammary cell, the bacteria evade more efficiently. However, when the cells are pre-infected by E. coli, MAP is rapidly attracted from the subepithelial region to the cell surface. IL-1β production enhances the attraction of macrophages to the site of infection, where MAP benefits by infecting them.